2019
DOI: 10.1016/j.ijppaw.2019.03.014
|View full text |Cite
|
Sign up to set email alerts
|

First report of Enterocytozoon bieneusi and Cryptosporidium spp. in peafowl (Pavo cristatus) in China

Abstract: Enterocytozoon bieneusi and Cryptosporidium spp. are important pathogens causing diarrhea in humans and animals. However, few studies have been conducted on the infection of E. bieneusi and Cryptosporidium spp. in peafowl up to now. The purpose of the present study was to determine the prevalence and the involved genotypes of Cryptosporidium spp. and E. bieneusi in peafowl in Beijing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 76 publications
0
4
0
3
Order By: Relevance
“…In China, genotype D has been identified in immunocompromized patients and in children with diarrhea [18,[27][28][29]32]. Genotype D has also been identified in a wide range of animal hosts in China, including non-human primates, rodents (mice, rats, squirrels, chipmunks, chinchillas, and bamboo rats), other mammals (pigs, cattle, sheep, goats, alpacas, horses, donkeys, rabbits, dogs, cats, foxes, deer, takins, minks, raccoon dogs, raccoons, lions, and hippos), and birds, as well as in water samples [6,8,9,11,17,24,26,30,31,33,34].…”
Section: Resultsmentioning
confidence: 99%
“…In China, genotype D has been identified in immunocompromized patients and in children with diarrhea [18,[27][28][29]32]. Genotype D has also been identified in a wide range of animal hosts in China, including non-human primates, rodents (mice, rats, squirrels, chipmunks, chinchillas, and bamboo rats), other mammals (pigs, cattle, sheep, goats, alpacas, horses, donkeys, rabbits, dogs, cats, foxes, deer, takins, minks, raccoon dogs, raccoons, lions, and hippos), and birds, as well as in water samples [6,8,9,11,17,24,26,30,31,33,34].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also reported much higher infection rates of Cryptosporidium in wild birds than this study, e.g., in wild captive psittacines in Brazil (10.64% 5/47), Java sparrows (Lonchura oryzivora) in northern China (13.42% 47/350), and North American red-winged blackbirds (Agelaius phoeniceus) (17.1% 12/70), and Canada geese (23.4% 49/209) in Ohio and Illinois [25][26][27][28]. Previous studies recorded Cryptosporidium infection rates in domestic birds of 2.3%-4.86% in Brazil [29][30][31] and 0.82%-8.1% in China [32][33][34][35][36]. These variations in the positive rate of Cryptosporidium in different studies may be attributable to population densities, feeding habits, and climate.…”
Section: Discussionmentioning
confidence: 99%
“…Although C. baileyi has been identified in one immunodeficient patient, this species should not be considered as a true zoonotic agent since this patient was immunodeficient, and no other reports exist (Ditrich et al, 1991). Cryptosporidium goose genotype I has been commonly found in Canada geese, and has also been found in aquatic birds and peafowl (Jellison et al, 2004; Zhou et al, 2004; Cano et al, 2016; Feng et al, 2019). To date, no human cases of cryptosporiosis caused by Cryptosporidium goose genotype I have been identified.…”
Section: Discussionmentioning
confidence: 99%